Central, Eastern and East-Central Europe: on the History and the Current State of Conceptualization and Demarcation of Concepts - Nataliya Antonyuk (Ksiegarnia Akademicka Publishing, 2019)
The article is devoted to a historical overview and discussion of the current understanding and demarcation of the concepts “Central Europe”, “Eastern Europe” and “Central Eastern Europe”. The analysis is performed from a descriptive and comparative point of view, including a step‑by‑step generalization and separation of the above concepts and the verification of how natural, artificial or instrumental their character is, as well as by analysing their contrastive properties. In conclusion, the author has argued that the integration / disintegration and democratization / autocratization processes in the countries that used to be or now constitute different sub‑regions of Europe during the 20th and 21st centuries have led to significant and highly ambiguous changes in the spectrum of political, socio‑economic, religious, cultural (national and supranational) processes, etc. As a result, various attributes of political, socio‑economic and cultural development, in particular their diversity from the perspective of certain European sub‑regions (which are often, though mistakenly, treated as a collective category of countries of “commensurable type”), have previously predetermined and today especially predetermine the need for analysis of the history and the current state of conceptualization and demarcation of the outlined concepts.